Curcumin Prevents Epithelial-to Mesenchymal Transition-Mediated Ovarian Cancer Progression through NRF2/ETBR/ET-1 Axis and Preserves Mitochondria Biogenesis in Kidney after Cisplatin Administration - Agian Jeffilano Barinda; Wawaimuli Arozal; Ni Made Dwi Sandhiutami; Melva Louisa; Nur Arfian; Normalina Sandora; Muhammad Yusuf (Tabriz University of Medical Sciences, 2022)
Purpose: Ovarian carcinoma is one of the gynaecological malignancies that have the highest mortality rates due to its progressivity. Endothelin signalling plays a leading role in the progression of ovarian cancer through Epithelial-to-Mesenchymal Transition (EMT). Cisplatin commonly used as potent chemotherapy; however, its application hindered by its nephrotoxic effect. Curcumin, a turmeric-derived compound, has an anticancer property, as well as a renal protective effect. Moreover, curcumin augments the affinity of the antioxidant enzyme, while inhibits endothelin-1 (ET-1) signalling. The effects of curcumin on ovarian cancer progression and cisplatin-induced kidney injury remain unknown. Methods: Curcumin was used as a supplementary therapy together with cisplatin in Human Ovarian Cancer Cell line (SKOV3) and also in rodent-induced ovarian cancer. The kidney phenotype in the ovarian cancer rat model after cisplatin ± curcumin administration will also be analyzed Results: Co-treatment of cisplatin with curcumin enhanced the expression of a gene involved in apoptosis in association with NRF2 enhancement, thus activated ETBR-mediated ET-1 clearance in SKOV3 cell and ovarian cancer model in rat. Moreover, curcumin treatment improved mitochondria biogenesis markers such as PGC-1α and TFAM and prevented the elevated of ET-1-mediated renal fibrosis and apoptosis in kidney isolated from cisplatin-treated ovarian cancer rat. Conclusion: Curcumin could be potentially added as an anticancer adjuvant with protective effects in the kidney; thus, improves the efficacy and safety of cisplatin treatment in the clinical setting.